2008
DOI: 10.1007/s10528-008-9177-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Variants of Extracellular Superoxide Dismutase Gene in a Romanian Population with Atheroma

Abstract: Extracellular superoxide dismutase (EC-SOD) is the main SOD isoform in the arterial wall contributing to cardiovascular defense against oxidative stress by removing the superoxide anion. In our study, the Thr40Ala and Arg213Gly polymorphic variants of the EC-SOD gene (SOD ( 3 )) were investigated for associations with atherosclerosis and other related factors in 144 subjects with significant atheroma (having one, two, or three major coronary arteries with >50% obstruction, and/or peripheral artery lesions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…An in vivo study reported that total serum cholesterol and obesity were associated with high common phenotype extracellular superoxide dismutase 44. Polymorphic variants of extracellular SOD gene are also reported to be associated with many diseases, such as hypertension,45 diabetes46 and certain cancers 47. Since inter‐individualized variation in antioxidant capacity may occur as a result of functional polymorphisms of genes regulating antioxidant enzyme activity, antioxidative processes may be more relevant as determinants of some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study reported that total serum cholesterol and obesity were associated with high common phenotype extracellular superoxide dismutase 44. Polymorphic variants of extracellular SOD gene are also reported to be associated with many diseases, such as hypertension,45 diabetes46 and certain cancers 47. Since inter‐individualized variation in antioxidant capacity may occur as a result of functional polymorphisms of genes regulating antioxidant enzyme activity, antioxidative processes may be more relevant as determinants of some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The SOD3 protein and mRNA are present in normal liver [95,96], and plasma levels are low in T2DM patients [90]. Moreover, a human polymorphism of SOD3, Ala40Thr, was reported to occur more often in T2DM patients than in nondiabetic controls and to be associated with a higher prevalence of hypertension and worse glucose handling in these patients [97,98]. Scavengers of intracellular H 2 O 2 include peroxiredoxin [61] and glutathione peroxidase [92], both of which have been shown to affect insulin signaling in vitro.…”
Section: Insulin-stimulated Nad(p)h Oxidase 4: Two Enzymatic Productsmentioning
confidence: 99%
“…Indeed, it has been postulated and partially shown, that oxidative stress in hypertension is due, at least in part, to the increase of NADPHox’s activity in vascular smooth muscle cells, fibroblasts and endothelial cells [14,15]. Polymorphisms of the genes codifying SOD and GPx have been related to oxidative stress due to decreased activity of the enzymes and high incidence of coronary artery disease [16], ischemic stroke [17,18] and atherosclerosis [19]. Polymorphisms of GST have been associated with cardiovascular events produced in smokers [20].…”
Section: Introductionmentioning
confidence: 99%